Effects of Ethrel, packaging and waxing on quality and shelf life of guava (Psidium guajava L.) fruits - Elkashif, Mohamed E; Hamdoun, Eltaya A.; Elamin, Osman M; Mahmoud, Haroon I (Gezira Journal of Agricultural Science; Vol 14 No 1 (2016), 2016)
Guava is one of the most popular fruits in the Sudan. It is usually harvested at the ripe stage which results in quick deterioration and huge post-harvest losses. Therefore, the objective of this work was to find out the effects of Ethrel, packaging and waxing on quality and shelf life of guava ( Psidium guanjava L.) fruits. Experiments were conducted at the University of Gezira, Wad Medani, Sudan, during December of 2013 and  March of  2014. Guava fruits were harvested at the mature-green stage and treated with Ethrel or left as control. Fruits were packaged in either intact or perforated polyethylene film, waxed or left unpackaged. The treatments were set up in a completely randomized design with two replicates. Results showed that Ethrel treatment significantly accelerated the rate of fruit ripening as shown by an increase in total soluble solids, skin colour development, vitamin C content, taste and a decrease in fruit firmness in both seasons. Packaging and waxing treatments had significant effects on weight loss, TSS, vitamin C content, firmness, taste and skin colour in both seasons. Packaging guava fruits in intact polyethylene film resulted in the lowest weight loss, followed by waxing, perforated polyethylene film and the highest weight loss was recorded for the control treatment in both seasons. The highest vitamin C  content, the best  skin colour and the longest shelf life were recorded in fruits packaged in intact polyethylene film followed by perforated, waxing and control treatments in both seasons. However, the highest TSS content, the best taste and the shortest shelf life were recorded for the control fruits in both seasons. It could be  recommended that, in order to prolong the shelf life and maintain the quality of guava fruits, they should be packaged in intact polyethylene film or waxed and treated with Ethrel at destination markets.     الجوافة من أكثر الفواكه شعبية في السودان. وهي عادةً تحصد في مرحلة النضج وهذا يؤدي إلى تدهورها السريع وعظم الفاقد ما بعد الحصاد. الهدف من هذا البحث هو العمل على دراسة تأثير الإثرل والتغليف والتشميع على نوعية وفترة صلاحية ثمار الجوافة. أجريت التجربة في جامعة الجزيرة، واد مدني، السودان خلال 2012/13 و2013/14. تم حصاد ثمار الجوافة في مرحلة البلوغ الأخضر ومعاملتها بالإيثرل أو تركها كشاهد. تم تغليف الثمار في أكياس بوليثين سليمة أو مخرمة أو تشميعها أو تركها كشاهد. صممت التجارب على نسق التصميم العشوائي الكامل بمكررين. معاملة الثمار بمادة الإثرل أدى إلى الإسراع في معدل نضج الثمار مما انعكس على زيادة محتوى المواد الصلبة الذائبة والتغيير في لون القشرة والزيادة الملحوظة في محتوى فيتامين ج وتحسين الطعم والانخفاض في صلابة الثمار في كلا الموسمين. معاملات التغليف بالبوليثين والتشميع كان لها تأثيرات معنوية على فقدان الوزن والمواد الصلبة الذائبة ومحتوى فيتامين ج وصلابة الثمار ومذاقها ولون القشرة في كلا الموسمين. تعبئة ثمار الجوافة في اكياس البولثين السليمة أدت إلى أقل فقدان في الوزن بتبعها التشميع ثم الكياس المخرمة وأكبر فقدان في الوزن لوحظ في الشاهد في كلا الموسمين. تعبئة ثمار الجوافة في أكياس البولثين السليمة أدت إلى أعلى محتوى من فيتامين ج وأفضل لون للثمار وأطول فترة صلاحية للثمار يتبعها الثمار المعبئة في الأكياس المخرمة ثم التشميع وأخيراً الشاهد في كلا الموسمين.  الثمار الغير مغلفة (الشاهد) أعطت أعلى محتوى من المواد الصلبة الذائبة وأفضل طعم ولكن أقصر فترة صلاحية في كلا الموسمين. للحصول على أطول فترة صلاحية لثمار الجوافة وتحسين جودتها ، يوصى بتعبئتها في أكياس بولثين سليمة أو تشميعها ومعاملتها بمادة الإثرل خصوصاً عند ترحيلها للأسواق البعيدة.